CITIZEN JOURNALISM: A STUDY OF NEW FORM OF NEWS MEDIA REPORTING - Akifah, Andi (Academica, 2012)
This paper explores the rise of participatory journalism as a newphase of media-based technology and its position in the journalismfield. As a new media form, citizen journalism appeared with a lot ofattraction supported by high technology that enables audiences to getfast information as well as flexibility in accessing it. It is examinedby comparing citizen journalists with professional journalists in theirway of gathering and reporting news. Apart from the benefits, thecitizen journalists particularly those who are considered as bloggersare sometimes challenged in providing accurate and objectiveinformation without being fully influenced by their thought. It isimportant to note that the collaboration between the citizen and theprofessional journalists is very essential to maintain the news qualitythey produce. Bloggers who work alone and provide information justbased on what they are thinking, without having any research, shouldbe considered as a separate term from other online reporters whowork based on journalism principles.Keywords: Citizen Journalism; Traditional media; News value;Internet; Technology.